Perancangan Ulang Tata Letak Untuk Pengoptimalan Ruang Pada Toko Ritel Abadi - Muhammad Rizky Firmansyah; Nengri Nengri; Putri Luciyani G; Queen Fadilla M (CV. KAMPUS AKADEMIK PUBLISING, 2024)
An important factor that supports the ease of a business in the long run is layout design. There is a problem at Abadi Retail Store, namely the improper layout of the storage warehouse. The improper layout of the storage warehouse causes stock items to be sent from the supply vehicle mode to the product display too far, which results in inefficient transfer of goods. The purpose of this research is to redesign the layout of the eternal retail store to improve employee performance and maximize the use of space. The method used is the Activity Relationship Chart (ARC) approach, Total Closeness Rating (TCR) and Layout Solution. The results of this study are, the placement of the storage warehouse layout in the layout solution needs to be changed and the results of the Total Closeness Rating (TCR) analysis show that the display rack has a TCR value of 168, while the storage warehouse has a TCR value of 112. So, the research shows that the storage warehouse should be placed closer to the display rack so that employees can place and arrange goods more efficiently.